Association mapping reveals novel genes and genomic regions controlling grain size architecture in mini core accessions of Indian National Genebank wheat germplasm collection - Kumari, Jyoti; Lakhwani, Deepika; Jakhar, Preeti; Sharma, Shivani; Tiwari, Shailesh; Mittal, Shikha; Avashthi, Himanshu; Shekhawat, Neelam; Singh, Kartar; Mishra, Kaushlesh Kumar; Singh, Rakesh; Yadav, Mahesh C.; et al. (Frontiers in Plant Science, 2023)
Wheat (Triticum aestivum L.) is a staple food crop for the global human population, and thus wheat breeders are consistently working to enhance its yield worldwide. In this study, we utilized a sub-set of Indian wheat mini core germplasm to underpin the genetic architecture for seed shape-associated traits. The wheat mini core subset (125 accessions) was genotyped using 35K SNP array and evaluated for grain shape traits such as grain length (GL), grain width (GW), grain length and width ratio (GLWR) and thousand grain weight (TGW) across the seven different environments (E1, E2, E3, E4, E5, E5, E6, and E7). Marker-trait associations were determined using multi-locus random-SNP-effect Mixed Linear Model (mrMLM) program. A total of 160 non-redundant quantitative trait nucleotides (QTNs) were identified for four grain shape traits using two or more GWAS models. Among these 160 QTNs, 27, 36, 38, 35 QTNs were associated for GL, GW, GLWR and TGW respectively while 24 QTNs were associated with more than one trait. Of these 160 QTNs, 73 were detected in two or more environments and were considered reliable QTLs for the respective traits. A total of 135 associated QTNs were annotated and located within the genes, including ABC transporter, Cytochrome450, Thioredoxin_M-type and hypothetical proteins. Furthermore, expression pattern of annotated QTNs demonstrated that only 122 were differentially expressed suggesting these could be potentially related to seed development. The genomic regions/ candidate genes for grain size traits identified in the present study represent valuable genomic resources that can be potentially utilized in the markers-assisted breeding programs to develop high-yielding varieties.